2012
DOI: 10.1002/lnc3.340
|View full text |Cite
|
Sign up to set email alerts
|

Vowel Harmony in Optimality Theory

Abstract: This article reviews the analysis of vowel harmony in Optimality Theory. Vowel harmony is a phenomenon in which the vowels in a word or another domain show systematic agreement for some property, such as rounding, backness, height, or ATR quality. Optimality Theory is a framework of generative linguistics in which grammars consist of a hierarchy of constraints on outputs. The treatment of various aspects of harmony systems are discussed, including what drives harmony, directionality and trigger control, opaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
1
15
0
1
Order By: Relevance
“…This is where the licensing part of LA comes into play. In section 3.1, I have already shown that assimilation may target prosodic/morphological domains rather than segments (Piggott and van der Hulst 1997, Hualde 1998, Piggott 2003, Walker 2011. That is to say, assimilation targets syllable nuclei, stressed syllables, or roots.…”
Section: Factorial Typologymentioning
confidence: 99%
See 1 more Smart Citation
“…This is where the licensing part of LA comes into play. In section 3.1, I have already shown that assimilation may target prosodic/morphological domains rather than segments (Piggott and van der Hulst 1997, Hualde 1998, Piggott 2003, Walker 2011. That is to say, assimilation targets syllable nuclei, stressed syllables, or roots.…”
Section: Factorial Typologymentioning
confidence: 99%
“…Yet the same licensing constraint is also satisfied by spreading from a pre-tonic segment (7a) or a segment in another word (7b). The challenge is that neither Ascrea nor any other language display such a pattern (Walker 2011). Positional licensing is generally not directional, predicting only bidirectional patterns.…”
Section: Prominence and Directionality In Non-parasitic Assimilationmentioning
confidence: 99%
“…Spreading-type constraints like Align [back] or Spread[back] generally require significant representational complexity, such as line crossing, gapped configurations, or output underspecification, to deal with transparency (e.g. Ringen & Vago 1998;Walker 1998;2012Jurgec 2011Ní Chiosáin & Padgett 2001). Further, constraints like Agree[back] do not have a natural way of referring to non-adjacent vowels, and they naturally prefer opacity to transparency in order to reduce the number of disharmonic transitions (Baković & Wilson 2000).…”
Section: The Nature Of the Harmony-driving Constraintmentioning
confidence: 99%
“…While considerable attention has been paid to distinguishing between these types (e.g. Kiparsky & Pajusalu 2003;Kimper 2011;Walker 2012;van der Hulst 2016), less research has focused on why neutrality occurs at all. In much of the literature, either implicitly or explicitly, the standard assumption is that a vowel will participate in harmony except when doing so is impossible due to a lack of harmonic counterpart in the inventory (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation